(untitled) (Journal of Medical & Health Sciences Review, 2025)
This paper explores the factors that influence preventive health behavior of urban adults based on awareness, availability, and socioeconomic issues. The cross-sectional design was the one used to collect data of 350 participants through a structured questionnaire. The findings indicated that the majority of the respondents had moderate knowledge on preventive health practices but this was not always translated to high levels of behavioral participation. The issue of accessibility became one of the most restrictive ones, and a considerable percentage of participants experienced difficulties regarding the solutions of affordability, distance, availability of services, and suitability of healthcare facilities. Socioeconomic inequalities also affected the patterns of preventive behaviors such that those with higher income and education levels would show more adherence to routine checkups, screenings, healthy living habits, among other preventive behaviors. The statistical analysis revealed that there were strong relationships between the awareness, accessibility, socioeconomic status, and preventive health behaviors, which implies that these factors interact to influence health outcomes in urban areas. The results highlight the importance of complex measures that should be undertaken to enhance health literacy, enhance healthcare infrastructure, and lower socioeconomic obstacles. When policymakers and health practitioners respond in a concerted effort to these determinants, preventive health engagement can be improved and healthier urban communities can be achieved.